A content analysis of literary evidence of slave trade in Zimbabwe focusing on Zimbabwean women’s trafficking to Kuwait. - Tsopo, Norma (Midlands State University, 2018)
The research is an investigation into the existence of trade in slaves in Zimbabwe in this era. The research will focus on the topical issue of trafficking of hundreds of Zimbabwean women to Kuwait as evidence of the continued existence of the practice which has been abolished for more than a millennium now. To clearly prove its case the study will investigate the issue by segmenting the practice into the three universally accepted elements that would constitute the existence of slavery which are – the act of owning someone; the methods of making someone one; and the purpose of enslaving someone. It will also make strong reference to historical accounts of slavery which will form the bedrock of slavery literature for reference against which the Zimbabwean accounts will be tested. Other proven present day accounts of slavery and trade in persons will be used to validate modern-day slavery practices. The study will take the form of a content analysis of literary accounts of slavery and slave trade from the antebellum era into present day accounts and media reports of accounts of trafficking of Zimbabwean women to Kuwait.